Produktivitas dan Pendapatan Usahatani Padi Sawah Tadah Hujan Di Kelurahan Cempaka Kota Banjarbaru - Yan Yozef Agus Suratman (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2020)
Optimization of rice productivity in paddy fields is one of the opportunities to increase national rice production. The not optimal productivity of rice in paddy fields, among others, is caused by various things, especially ethanol rice farming, which faces technical, social, and economic obstacles to develop a more profitable rice commodity. Fertilization management practices greatly affect productivity, if productivity is increased, resulting in higher income and enabling farmers to save and accumulate capital. The income earned by a farmer is the reward that the farming family receives from the use of production factors, labor, and capital invested in the business sector. This study aims to determine (i) the productivity of rainfed lowland rice farming, (ii) explicit costs, revenues, and income of rainfed lowland rice farming in Cempaka Village, Cempaka District, Banjarbaru City, South Kalimantan Province. The research was conducted from March-May 2020. The method used in this study was a survey method with observational techniques, where the sampling technique was carried out by simple random sampling of 217 households taken 14% so that 30 respondents were obtained. The results showed that the productivity of rainfed lowland rice farming was 1,265.00 kg/respondent or 3.5 tons/ha. The average explicit cost is Rp. 1.751.506,83 / respondent or Rp. 4.865.296.74 / ha, the average revenue of Rp. 6.325.000 / respondent or Rp. 17.569.444,44 / ha and an average income of Rp. 4.573.493,17 / respondent or Rp. 12.704.147,71 / ha.